Degradation of surfactant waste of leather tanning using Fe2O3/activated carbon catalyst - Shinta Amelia; Witri Rahmadani; Laeli Rizki Amalia; Zahrul Mufrodi (Majalah Kulit, Karet, dan Plastik, 2019)
The development of the tannery industry in addition to being beneficial for the economic growth of the community also has a negative impact on the environment due to the disposal of waste produced. Components of waste produced from the leather tanning industry include residual protein and fat, surfactants, anti-bacterial, anti-fungal, coloring and tanning agents. One component that is found in surfactants and often pollutes waters is alkyl benzene sulfonate and linear alkyl benzene sulfonate surfactants. Alkyl benzene sulfonate (ABS) is an anionic surfactant that has a very long and branched carbon chain that is difficult to degrade by microorganisms in nature. Characterization and testing of the activity of porous/activated carbon catalysts will be carried out. The type of porous activated carbon used is coconut shell carbon with microspores character. The stages of this research consisted of the process of impregnation of iron oxide on porous carbon, the surfactant waste degradation process and the characterization of the catalysts produced. Based on the research that has been done, it can be concluded that the catalyst Fe2O3/coconut shell activated carbon is very effective to be applied for the degradation of surfactant waste. The degradation capacity of surfactant wastes increases with increasing concentration of active site Fe. The capacity of the surfactant waste degradation reaction using coconut shell catalyst at t = 3 hours for variations in the concentration of Fe 2%, 4% and 6% respectively 6.77 mmol/gram catalyst, 3.18 mmol/gram catalyst and 1.61 mmol/gram catalyst. The data show that the surfactant waste degradation reaction capacity increases with the increase in the composition of iron oxide added to the surface of the porous carbon support.